New species of Chilean Hexathelidae (Araneae, Mygalomorphae) - Ríos Tamayo, Duniesky (2012)
Several new species of Hexathelidae Simon (1892) from Chile are described. In Scotinoecus Simon (1892), a new species (S. ruiles) is described using females; a new species (S. major) is proposed for the male previously misidentified as S. cinereopilosus(Simon, 1889), and females are described; the male of S. cinereopilosusis described for the first time. In Mediothele, the female of M. australisis described for the first time, as well as five new species (M. minima,M. linares, M. nahuelbuta,M. anae andM. lagos); all are based solely on females from Southern and Central Chile. The known geographic distributions of both genera are increased.